Biological activities and in vitro digestion characteristics of glycosylated α-lactalbumin prepared by microwave heating: Impacts of ultrasonication. (15th March 2022) - Ma, Yue; Liu, Yue; Yu, Haiying; Mu, Sinan; Li, Hongyu; Liu, Xianqi; Zhang, Minghan; Jiang, Zhanmei; Hou, Juncai
Abstract: The research focuses on application of ultrasonic-assisted glycosylation in food protein modification. Biological activities and in vitro digestion characteristics of the glycosylated α-lactalbumin (UMGLA) and α-lactalbumin (UMLA) prepared by ultrasonic pretreatment and microwave heating at 85 °C for 2 h were investigated mainly through the browning degree, free amino group, reducing sugar and surface hydrophobicity, in vitro digestibility and degree of hydrolysis, total antioxidant capacity, α-glucosidase inhibitory activity, xanthine oxidase inhibitory activity determination methods. The results showed that ultrasonic pretreatment could effectively promote the occurrence of glycosylation reaction, reduce in vitro digestibility and degree of hydrolysis of glycosylated α-lactalbumin and enhance biological activities of glycosylated α-lactalbumin digestive products. Furthermore, after 60 min of ultrasound treatment, the total antioxidant capacity and α-glucosidase inhibitory activity of glycosylated α-lactalbumin digested products were increased by 76.52 ± 0.02% and 12.42 ± 0.04%, respectively, compared with α-lactalbumin without ultrasound treatment. In conclusion, ultrasonic-assisted glycosylation had positive effects on improving the biological activities of in vitro digestion product of α-lactalbumin. It provides a theoretical basis for ultrasonic-assisted glycosylation in the modification field of food proteins. Graphical abstract: Image 1 Highlights: Ultrasonic pretreatment can promote the glycosylation of α-LA and xylose Digestibility and degree of hydrolysis of glycosylated α-LA reduced by ultrasound. Ultrasound enhanced biological activities of glycosylated α-LA digested products